AKULTURASI BUDAYA JAWA DAN ISLAM MELALUI DAKWAH SUNAN KALIJAGA - Naufaldi Alif; Laily Mafthukhatul; Majidatun Ahmala (Al'Adalah, 2020)
The culture of the people in Nusantara (Java) seems to be acculturated with Islam. Both have merged into a distinctive culture with certain characters. This acculturation is related to the preaching of Walisongo, especially Sunan Kalijaga, in spreading Islam in Java. By considering local culture, he preaches Islam by not coercing the community. The local community also welcomed it so that Islam was widespread in Java. Sunan Kalijaga believes that if people already understand Islam, then automatically these old habits will be replaced with better ones. Therefore, it is not surprising that Sunan Kaliaga's teachings tend to be syncretic in introducing Islam by combining Javanese culture and Islamic teachings so that there is harmony between the two. In the end, the syiar of Islam was easily accepted by the community because it accommodated elements of local community values.